Optimal dose of vigorous physical activity on cardiorespiratory and perceptual response for sedentary youths using internal load monitoring - Haohan Yu; Yue Gao; Jiaxin Liang; Yiming Fan; Shan Jiang (Frontiers in Physiology, 2024)
IntroductionVigorous physical activity (VPA) has been demonstrated to enhance cardiorespiratory fitness (CRF) in sedentary college students more effectively than other PA. However, differences in training volume may affect this outcome. This study examines the physiological, psychological, and internal training load (ITL) characteristics of VPA with varying volumes in a single session.MethodsThirty sedentary college students were divided into three groups: high-intensity interval training (HIIT), sprint interval training (SIT), and threshold training (THR). PA process was monitored. The study measured various cardiorespiratory parameters, including heart rate (HR), respiratory waveform and amplitude, respiratory rate (RR), tidal volume (TV), minute ventilation volume (VE), fractional concentration of oxygen in end-tidal gas (O2%), fractional concentration of end-tidal carbon dioxide (CO2%), global oxygen consumption (VO2), carbon dioxide discharge (VCO2), and the amount of carbon dioxide in the air. The following physiological indicators were measured: carbon dioxide discharge (VCO2), Oxygen pulse (OP), and respiratory exchange ratio (RER). Additionally, subjective perception indicators were recorded, including the feeling scale (FS), rating of perceived exertion (RPE), and dual-mode model (DMM). The session-RPE (s-RPE) and Edward's TRIMP were used to measure ITL.ResultsThere were no significant differences in HR across the three conditions. THR had the highest level of TV (p = 0.043), but RR was significantly lower than that of HIIT and SIT (p < 0.01). HIIT had the highest levels of VO2, VCO2, O2%, and OP (p < 0.05). RPE was higher in HIIT and SIT compared to THR (p < 0.01), but the difference in FS was not significant. The DMM time-domain trajectories were similar in HIIT and THR. The correlation between exercise intensity, RPE, and FS was highest in THR group (r = 0.453, r = −0.58, r = −0.885). ITL did not show a significant difference between three conditions, but TRIMP and s-RPE readings were opposite in magnitude.ConclusionThis study proposes that using an appropriate amount of THR to foster interest and adaptive strength during the PA habit establishment period, incorporating HIIT to enhance exercise efficiency during the adaptation period, and implementing SIT to reduce the monotony may effectively enhance the cardiorespiratory fitness of sedentary college students and establish PA habit.